PEMBENTUKAN BUDAYA POPULER DALAM KEMASAN MEDIA KOMUNIKASI MASSA - Inda Fitryarini (Jurnal Ilmiah Komunikasi Makna, 2012)
Culture is people’s way of life, views and values. Learning about culture means learning about language, communication and elements of culture,  but more than that culture in our world today deals with what are the trends and act as popular items. We acknowledge popular culture as the culture that represents insubordination towards society’s strict old way of life.  Popular culture is what we eat, drink, sleep with, watch, and act with. The writer trids to read the reality built in popular culture and otherwise popular culture as a reality. Writer found that popular cultures are not just about people, language, fashion or even life necessities. Popular culture has its root in commercial values and likewise. Populer culture bears the burden of producing something that worth commercially. In return, popular culture held the identification of a society as a unity. What someone wears identify whether certain someone are a part of a popular society or not.Keywords: popular culture, mass communication, televisi